Porokeratosis ptychotropica: successful treatment with the dermatome - Scheiba, Nina; Enk, Alexander; Proske, Sylvia; Hartschuh, Wolfgang (Dermatologic surgery, 2010)
Annular plaques with a keratotic border that expands peripherally, leaving an atrophic center, clinically characterize porokeratosis. Histopathologically, the cornoid lamella is the pathognomonic feature for the diagnosis. Porokeratosis may be inherited in an autosomal dominant way, but sporadic cases have been described as well.